Pengaruh Kurikulum Operasional Satuan Pendidikan, Kompetensi Guru Dalam Meningkatkan Karakter Peserta Didik Melalui Profil Pelajar Pancasila - Herni Indraswari; Vip Paramarta; Theresia Widyanti (Journal on Education, 2024)
This study aims to present a comprehensive overview of the influence of the Operational Curriculum of Educational Units and teacher competencies on Student Character through the Pancasila Student Profile in State Elementary Schools in the Cibeunying Kidul District of Bandung City. The method used is inferential, involving 47 teachers from State Elementary Schools in Bandung City as the research sample. Data processing was conducted using Smart PLS 4 Software. The main findings of the study indicate that the Operational Curriculum of Educational Units does not influence student character, while teacher competencies significantly influence student character. Furthermore, the Operational Curriculum of Educational Units does not affect the Pancasila Student Profile, whereas teacher competencies have a significant effect on the Pancasila Student Profile. The Pancasila Student Profile does not influence student character. Moreover, the Operational Curriculum of Educational Units' influence on student character through the Pancasila Student Profile and teacher competencies' influence on student character through the Pancasila Student Profile have no effect. Finally, there is an influence of the Operational Curriculum of Educational Units, teacher competencies, and the Pancasila Student Profile simultaneously on student character.